Pengaruh Kemampuan Kerja Dan Motivasi Kerja Melalui Reward System Terhadap Kinerja Pegawai Sekretariat Daerah Kabupaten Magetan - Afrila Kurnia Dhani; M.Farid Wajdi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to evaluate the influence of work ability and work motivation on employee performance through the implementation of a reward system at the Regional Secretariat of Magetan Regency. Using a quantitative approach, data were collected through questionnaires distributed to employees. The research sample was selected using a simple random sampling technique. The variables analyzed include Work Ability, Work Motivation, Reward System, and Employee Performance. Data analysis was conducted using the Partial Least Square (PLS) method to examine the relationships between variables. The findings indicate that work ability and work motivation have a significant positive effect on employee performance, while the reward system does not show a significant impact. The limitations of this research lie in the scope of respondents, which only includes employees of the Regional Secretariat of Magetan Regency, as well as variations in work tenure, educational background, and job positions that may influence respondents’ perceptions.